Raising the Bar for the Mens Rea Requirement in Common Intention Cases: Daniel Vijay s/o Katherasan v PP - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2011)
Recently, the Court of,4ppeal in Daniel Vijay s/o Katherasan v. Public Prosecutor took the view thatthe law on common intention was not adequately settled in Singapore despite the 138-year history ofs. 34 ofthe Penal Code. It went on to give an extensive review of the cases interpreting the section aswell as its Indian equivalent, before setting out the proper approach to take in "twin crime" commonintention cases, focusing specifically on the mens rea element required in order to establish constructiveliabilityfor the secondary crime. This case note seeks to highlight the changes brought about byDaniel Vijay s/o Katherasan v. Public Prosecutor andto comment on the significance ofthese changes.